Urinary Polymerase Chain Reaction for Diagnosis of Urogenital Tuberculosis - Yazdani, Mohammad Yazdani; Shahidi, Shahrzad Shahidi; Shirani, Majid Shirani (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman"; mso-fareast-font-family:"Times New Roman"; mso-bidi-language:FA; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The aim of this study was to evaluate diagnostic value of urinary polymerase chain reaction (PCR) in urogenital tuberculosis (UTB). Materials and Methods: In 33 patients with confirmed diagnosis of UTB by urine culture and/or acid-fast staining, clinical symptoms and laboratory and radiological findings were evaluated. For each patient, 3 consecutive urine samples were examined by PCR for Mycobacterium tuberculosis and the results were compared with the standard microbiological methods and radiological findings. Results: The mean interval between the appearance of the symptoms and the diagnosis was 12.3 Â± 12.2 months. Symptoms were irritative bladder symptoms such as dysuria and diurnal or nocturnal frequency (51.5%), flank pain (27.3%), microscopic hematuria (18.2%), gross hematuria (9.1%), and suprapubic pain (9.1%). The laboratory findings included hematuria (27.3%), pyuria (12.1%), and hematuria with pyuria (48.5%). Diagnosis of UTB was made in 19 patients by positive urine culture for MT in 19 patients (57.6%), positive acid-fast staining in 6 (18.2%), and both in 8 (24.2%). Intravenous urography showed abnormal findings in 16 patients (61.5%), including pyelocaliceal dilatation (26.9%), ureteral stricture and hydroureter (23.1%), multiple small caliceal deformities (15.4%), severe parenchymal destruction (11.5%), autonephrectomy (11.5%), and calcification (7.7%). Urinary PCR was positive in 16 patients (48.5%) and in 10 (62.5%) with abnormal findings on intravenous urography. Conclusion: A high index of suspicion is necessary for diagnosis of UTB even in patients with nonspecific manifestations. Urinary PCR is recommended for instant diagnosis and screening before further examinations, but it cannot be the sole diagnostic modality for diagnosis of UTB.